2003
DOI: 10.1242/jeb.00571
|View full text |Cite
|
Sign up to set email alerts
|

The retina ofManduca sexta: rhodopsin expression, the mosaic of green-, blue- and UV-sensitive photoreceptors, and regional specialization

Abstract: in the compound eye of Manduca sexta were verified by immunocytochemistry, and the retinal mosaic was mapped, using polyclonal antisera raised against aminoterminal sequences of three identified rhodopsins: P520, P450 and P357. Retinulae are composed of a small proximal cell and seven or eight elongate cells extending across the retina. In each retinula, one or two elongate dv cells oriented in the dorsal-ventral axis of the retinal lattice express either P450 or P357. Six elongate ap and ob cells in the anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 55 publications
7
82
0
Order By: Relevance
“…Yet, we have to consider the possibility that we did not pick up the responses of a rare or small photoreceptor type, especially if it was located far from our electrode. Lepidopterans typically possess stacked receptors with one cell contributing only to the proximal part of the retina (Briscoe, 2008;White et al, 2003, Belušič et al, 2017. In the African armyworm moth, Spodoptera exempta, the basal cell is maximally sensitive to wavelengths of 560 nm (Langer et al, 1979;Meinecke & Langer, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, we have to consider the possibility that we did not pick up the responses of a rare or small photoreceptor type, especially if it was located far from our electrode. Lepidopterans typically possess stacked receptors with one cell contributing only to the proximal part of the retina (Briscoe, 2008;White et al, 2003, Belušič et al, 2017. In the African armyworm moth, Spodoptera exempta, the basal cell is maximally sensitive to wavelengths of 560 nm (Langer et al, 1979;Meinecke & Langer, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary analyses of chromatic contrast for all possible combinations of abundances between 1:1:1 to 1:4:10 (for the UV:blue:green receptors; upper limit derived from data on the tobacco hornworm, Manduca sexta, cf. White et al, 2003) and absolute noise between 0.08 and 0.12 (cf. Vorobyev et al, 2001) indicated, without exceptions, lowest contrast for 1:1:10, 0.12 (receptor contrast, absolute noise), and highest contrast for 1:4:1, 0.08.…”
Section: Modelling Chromatic Contrastmentioning
confidence: 99%
“…The presence of a fourth visual pigment mRNA BRh2, together with UVRh and BRh1, furnishes Lycaena with six ommatidial subtypes in the ventral eye area (Fig.·4), twice the number found in any other lepidopteran (Arikawa, 2003;Briscoe et al, 2003;White et al, 2003;Sauman et al, 2005;Zaccardi et al, 2006). Even in Pieris rapae (Arikawa et al, 2005), which as noted above has independently evolved a violet receptor from a duplicate blue opsin gene, only three ommatidial types have been reported: those expressing UV-UV, UV-B, and V-V opsin mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the unusual BRh1 mRNA expression in the outer R3-8 photoreceptor cells of the L. rubidus dorsal eye, the typical lepidopteran expresses short wavelength opsin mRNAs only in the R1 and R2 cells (Kitamoto et al, 2000;Briscoe et al, 2003;White et al, 2003;Sauman et al, 2005). Closer inspection of UVRh, BRh1 and BRh2 expression in individual ommatidia indicated that these transcripts are also present in the R1 and R2 photoreceptor cells of both sexes (Fig.·4).…”
Section: Non-overlapping Expression Of Uvrh Brh1 and Brh2mentioning
confidence: 98%
See 1 more Smart Citation